Correction of a Posttraumatic Orbital Deformity Using Three-Dimensional Modeling, Virtual Surgical Planning with Computer-Assisted Design, and Three-Dimensional Printing of Custom Implants. Issue 1 (March 2018) - Day, Kristopher M.; Phillips, Paul M.; Sargent, Larry A.
We describe a case of complex, posttraumatic skull and orbital deformities that were evaluated and treated with advanced computer technology, including virtual surgical planning, three-dimensional (3D) modeling, and printed patient custom implants (PCI) fabricated by 3D printing. A 50-year-old man presented to our craniofacial referral center 1 year after failed reduction of complex left orbital, zygomatic, and frontal bone fractures due to a motorcycle collision. The patient's chief complaint was debilitating diplopia in all fields of gaze. On examination, he had left enophthalmos, left canthal displacement, lower eyelid ectropion, vertical orbital dystopia, and a laterally and inferiorly displaced, comminuted zygoma with orbital rim and frontal bone defects. The normal orbit was mirrored to precisely guide repositioning of the globe, orbital reconstruction, and cranioplasty. Preinjury appearance with normal globe position was restored with complete resolution of diplopia. Modern 3D technology allows the surgeon to better analyze complex orbital deformities and precisely plan surgical correction with the option of printing a PCI. These techniques were successfully applied to resolve a case of debilitating diplopia and aesthetic deficits after facial trauma. Further application of advanced 3D computer technology can potentially improve the results of severe orbital and craniofacial trauma reconstruction.